(untitled) (Journal of Geography and Environmental Management, 2018)
Atmospheric precipitation has an important role in formation of the chemical composition of natural waters. On the one hand, an atmospheric precipitation is a direct source in reservoirs of many chemical elements, with another – interaction of rainfall with soils and breeds on a reservoir leads to additional enrichment of natural waters chemicals. Clarification of a role of rainfall in formation of the chemical composition of natural waters is of great importance for understanding of functioning of water ecosystems. Loss of the atmospheric precipitation which is the primary source of a surface water in very big measure influences also the chemical composition of the last. The comparative characteristic of the chemical composition of atmospheric precipitation is given during 1985-1996 and 2000-2011 according to the data of weather stations in the Ili-Balkhash basin. Recently pollutants has been increased, including some heavy metals have exceeded threshold limit value.